An EIS for the analysis of vulnerability of water storage tanks to natural hazards. Issue 4 (1st October 2016) - Hammoum, Hocine; Bouzelha, Karima; Touat, Mouloud; Pantet, Anne
Abstract: The concept of vulnerability to some natural hazards (snow, wind and earthquakes) is used in this paper to predict the level of degradation or ageing that may occur on a large scale to a water storage tank. To assess the state of these tanks, our research is based on a diagnostic method which consists in determining the index of vulnerability, taking into account all the influential parameters: environmental, structural and functional. From this index, we propose a scale of classification of tanks in three levels of behaviour (good, average, bad), and each level is associated with a different colour. Additionally, we have constructed an environment information system (EIS) – that is, a computer application associated with a geographic information system (GIS) to allow tank managers to handle the matter, and analyse, display and visualise the data well. The tanks to which we have tied the geo-referenced information are implanted as focal point objects. Therefore, the produced system constitutes for managers of storage structures a tool to reach conclusions and make decisions. In other words, the system informs us about the attention that should be given to vulnerable structures after a thematic analysis. It also allows us to better visualise the priorities of the structures that need rehabilitation. For the needs of the study, 22 tanks are investigated in Tizi-Ouzou, Algeria.